Lucy's flat feet: the relationship between the ankle and rearfoot arching in early hominins. - Jeremy M DeSilva (Public Library of Science (PLoS), 2010)
Background In the Plio-Pleistocene, the hominin foot evolved from a grasping appendage to a stiff, propulsive lever. Central to this transition was the development of the longitudinal arch, a structure that helps store elastic energy and stiffen the foot during bipedal locomotion. Direct evidence for arch evolution, however, has been somewhat elusive given the failure of soft-tissue to fossilize. Paleoanthropologists have relied on footprints and bony correlates of arch development, though little consensus has emerged as to when the arch evolved. Methodology/principal findings Here, we present evidence from radiographs of modern humans (n = 261) that the set of the distal tibia in the sagittal plane, henceforth referred to as the tibial arch angle, is related to rearfoot arching. Non-human primates have a posteriorly directed tibial arch angle, while most humans have an anteriorly directed tibial arch angle. Those humans with a posteriorly directed tibial arch angle (8%) have significantly lower talocalcaneal and talar declination angles, both measures of an asymptomatic flatfoot. Application of these results to the hominin fossil record reveals that a well developed rearfoot arch had evolved in Australopithecus afarensis. However, as in humans today, Australopithecus populations exhibited individual variation in foot morphology and arch development, and "Lucy" (A.L. 288-1), a 3.18 Myr-old female Australopithecus, likely possessed asymptomatic flat feet. Additional distal tibiae from the Plio-Pleistocene show variation in tibial arch angles, including two early Homo tibiae that also have slightly posteriorly directed tibial arch angles. Conclusions/significance This study finds that the rearfoot arch was present in the genus Australopithecus. However, the female Australopithecus afarensis "Lucy" has an ankle morphology consistent with non-pathological flat-footedness. This study suggests that, as in humans today, there was variation in arch development in Plio-Pleistocene hominins.